2017
DOI: 10.3390/su9010097
|View full text |Cite
|
Sign up to set email alerts
|

Sprinkling: An Approach to Describe Urbanization Dynamics in Italy

Abstract: This paper presents research which has defined a new typology of urban patterns (sprinkling), different from the internationally recognized standard urban sprawl, as well as various indicators that have been implemented to measure sprinkling. It is important to highlight that the damage caused to the environment and communities by urban sprinkling is much more serious and irreversible than that notoriously caused by urban sprawl. The paper introduces the difficult methodological and planning aspects of retrofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…The method illustrated here is based on research that showed the rate of land conversion into urban areas in Italy over half a century [1]. It provides a series of data, unprecedented for their level of detail, and it refers to the 1950s decade.…”
Section: Introductionmentioning
confidence: 99%
“…The method illustrated here is based on research that showed the rate of land conversion into urban areas in Italy over half a century [1]. It provides a series of data, unprecedented for their level of detail, and it refers to the 1950s decade.…”
Section: Introductionmentioning
confidence: 99%
“…This process of speculative urban growth related to neoliberal capitalism is of great interest for the above-mentioned scholars focused on urban studies [35][36][37][38]. Spain is a good example of it within the urban sciences in recent years and the phenomenon has been analyzed as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…This is true, for example, in large regions of the Continental Portuguese territory, where urban diffusion largely consisted of a large land take with a partially spontaneous development, or subject to low controls, adding on to a historical structure. This artificialization pattern, characteristic of very low human population densities, was initially defined as sprinkling by Romano and Zullo (2016) in the Po Valley and later analyzed in the whole Italian territory (Romano et al, 2017a). These newly built-up areas account for a small fraction of the total territory.…”
Section: Introductionmentioning
confidence: 99%